1987
DOI: 10.5962/bhl.part.349
|View full text |Cite
|
Sign up to set email alerts
|

Comment on the proposed suppression for nomenclatural purposes of three works by Richard W Wells and C. Ross Wellington

Abstract: We support the request by ) that the senior name, Simulium posticatum Meigen, 1838, should retain precedence over the junior name 5". austeni Edwards, 1915. In our recent pubHcations and reports on ecological studies relating to this species we have adopted the nomenclatural change proposed by Zwick & Crosskey (1981). Reversion to the use of austeni, as proposed by Rubtsov, would compound the confusion associated with name changes to a species of local severe pest status. We urge the Commission to reject the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The name Acanthophis armstrongi has not given rise to much discussion since its initial establishment. Shea (1987), Aplin (1999), and Aplin & Donnellan (1999) regarded it as a nomen nudum, noting that Storr (1981) treated the populations concerned as part of his concept of A. pyrrhus, without any attempt to differentiate between populations. The name has remained unused in the peer-reviewed scientific literature (sensu Kaiser et al 2013) since then.…”
Section: Availability Of Acanthophis Armstrongi Wells and Wellington 1985mentioning
confidence: 99%
See 2 more Smart Citations
“…The name Acanthophis armstrongi has not given rise to much discussion since its initial establishment. Shea (1987), Aplin (1999), and Aplin & Donnellan (1999) regarded it as a nomen nudum, noting that Storr (1981) treated the populations concerned as part of his concept of A. pyrrhus, without any attempt to differentiate between populations. The name has remained unused in the peer-reviewed scientific literature (sensu Kaiser et al 2013) since then.…”
Section: Availability Of Acanthophis Armstrongi Wells and Wellington 1985mentioning
confidence: 99%
“…Wells & Wellington (1985) named A. lancasteri from the Kimberley region of Western Australia (WA) and the 'Top End' of the Northern Territory (NT). Several authors (Shea 1987;Aplin 1999;Aplin & Donnellan 1999;Maddock et al 2015;Wüster, 2021) have explicitly considered A. lancasteri a nomen nudum: the diagnosis was outsourced to Storr (1981), but in these authors' view, Storr did not provide diagnoses compliant with Article 13 of the International Code of Zoological Nomenclature (hereafter, the Code; ICZN 1999), making the species epithet lancasteri unavailable. Shea (1987: 258) identified A. lancasteri as one of the many species described by Wells & Wellington (1985), for which "the attempted diagnosis of new species on the basis of previously published photographs or previously published descriptions [does] not provide a statement in words of characters that are purported to differentiate the taxon (Article 13a (i-ii)," and he further stated (p. 259) that "In a few of these cases, the publication cited provides a diagnosis of the taxon in question as part of a redescription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The works by Wells & Wellington (1984, 1985 were the subject of a case presented to the International Commission for Zoological Nomenclature for suppression for nomenclatural purposes by the Australian Society of Herpetologists (1987). In a separate submission Shea (1987) independently assessed the validity of actions contained in these works, and with regard to the description of Contundo roomi found that while the diagnosis presented was unworkable, it did not prevent the availability of this name under the code. The ICZN (1991) considered these works by Wells & Wellington to represent a "clear rejection of virtually every tenet of the voluntary code of ethics", but ruled that the legitimacy of the taxa proposed be determined on a case by case basis against the rules of the ICZN.…”
Section: Recognition Of Egernia Roomi For the Kaputar Rock Skinkmentioning
confidence: 99%
“…nov." pending "completion of studies on the Egernia striolata complex by G. Shea". No comment was given as to why this action was taken in precedence over the earlier statement by Shea (1987) regarding the availability of the name. The only other mention of the name roomi is by Cogger (2014) under the account of subspecies of Egernia saxatilis, but only in that its status was uncertain.…”
Section: Recognition Of Egernia Roomi For the Kaputar Rock Skinkmentioning
confidence: 99%